Analysis of Indonesian Trade: Case Study After The AFTA Agreement - Poetra, Ronald Pratama (Universitas Airlangga, 2019)
The ASEAN Free Trade Area (AFTA) began in 1993. The hope of this agreement was that intra-ASEAN trade to grow rapidly turned out to be slow. Based on data from the ASEAN Secretariat in 2016, intra-ASEAN trade experienced a slow journey in the range of 20-24 percent over the past few years. This study empirically analyzed the influence of AFTA on Indonesia's trade structure towards ASEAN using TSI, GL / IIT, and CTB index. In the period of 2012-2017 Indonesia's trade balance against ASEAN suffered a loss. Despite the loss, there was a decrease in trade balance losses from 2015-2017 (after AFTA). To analyze trade there are 10 commodity classifications determined by SITC revision 3. Based on the results of the TSI analysis, there is a specialization of 6 commodities trading which have high export power. The CTB analysis is only commodities of Chemicals and related products, n.e.s, which contribute positively to Indonesian trade. For IIT analysis there are 4 commodities where the average IIT index increases after the AFTA agreement. Keywords: ASEAN, Trade, AFTA, IIT, TSI, CTB JEL Classification: F180, F140, F130